Biosynthesis of the Essential Fatty Acid Oxidation Cofactor Carnitine Is Stimulated in Heart and Liver after a Single Bout of Exercise in Mice - Tom L. Broderick; Frank A. Cusimano; Chelsea Carlson; Jeganathan Ramesh Babu (Journal of Nutrition and Metabolism)
We determined whether one single bout of exercise stimulates carnitine biosynthesis and carnitine uptake in liver and heart. Free carnitine (FC) in plasma was assayed using acetyltransferase and [14C]acetyl-CoA in Swiss Webster mice after 1 hour of moderate-intensity treadmill running or 4 hours and 8 hours into recovery. Liver and heart were removed under the same conditions for measurement of carnitine biosynthesis enzymes (liver butyrobetaine hydroxylase, γ-BBH; heart trimethyllysine dioxygenase, TMLD), organic cation transporter-2 (OCTN2, carnitine transporter), and liver peroxisome proliferator-activated receptor-alpha (PPARα, transcription factor for γ-BBH and OCTN2 synthesis). In exercised mice, FC levels in plasma decreased while heart and liver OCTN2 protein expressed increased, reflecting active uptake of FC. During recovery, the rise in FC to control levels was associated with increased liver γ-BBH expression. Protein expression of PPARα was stimulated in liver after exercise and during recovery. Interestingly, heart TMLD protein was also detected after exercise. Acute exercise stimulates carnitine uptake in liver and heart. The rapid return of FC levels in plasma after exercise indicates carnitine biosynthesis by liver is stimulated to establish carnitine homeostasis. Our results suggest that exercise may benefit patients with carnitine deficiency syndromes.